Keimanan Kristus dalam Peraturan Melkisedek: Sebuah Upaya Rekontruksi Kristologi Keimanan dalam Ibrani 7: 1-10 - Rena Sesaria Yudhita (Faculty of Theology Duta Wacana Christian University, 2016)
Abstrak Hebrews has a distinctive christology denoting Christ’s particular priesthood. The fact that Jesus is not qualified in anyway to be a priest according the Aaronic order is inevitable. Therefore, the author composed an argument that the foundation of Christ’s priesthood isthe order of Melchizedek. This article seeks to examine how the Hebrew’s author recognize, interpret, and utilize the character of Melchizedek to build his unique priesthood christology. The efforts are made by interpreting Hebrews 7:1-10, in which the author shows the significance of the Melchizedek’s figure to the Jesus’ priesthood. First, this article investigate show the author of Hebrews uses Melchizedek mysterious character in Genesis and Psalm are echoed in verses 1-3 and then examine the christology of priesthood developed in verses 4-10. Basically the character of Melchizedek was still shrouded in mystery even to the end of the study. However, precisely in this mystery we can see how ingenious the author is. Abstrak Surat Ibrani memiliki kristologi unik yang menunjukkan peran imamat Sang Kristus. Namun tak bisa disangkal jika Yesus tak memenuhi kualifikasi keimaman menurut peraturan Harun. Karena itu, penulis Ibrani menyusun argumentasi bahwa dasar dari keimaman Yesus adalah peraturan Melkisedek. Artikel ini berupaya untuk meneliti bagaimana penulis Ibrani mengenal, menafsirkan, dan menggunakan karakter Melkisedek untuk membangun kristologi keimamannya. Upaya ini dilakukan dengan cara menafsir Ibrani 7:1-10 di mana penulis Ibrani menunjukkan signifikansi karakter Melkisedek terhadap peran keimaman Yesus. Pertama, artikel ini menyelidiki bagaimana penulis Ibrani menggunakan misteri karakter Melkisedek dalam Kejadian dan Mazmur yang digemakan dalam ayat 1-3 dan kemudian memeriksa konstruksi kristologi keimaman yang dikembangkan dalam ayat 4-10.Pada dasarnya, karakter Melkisedek masih diliputi misteri bahkan hingga akhir penelitian ini. Namun, justru dalam misteri inilah kita dapat melihat bagaimana cerdasnya penulis Ibrani memainkan imajinya dalam figur Melkisedek.